Differential contributions of body form, motion, and temporal information to subjective action understanding in naturalistic stimuli - Smekal, Vojtěch; Poyo Solanas, Marta; Fraats, Evelyne I. C.; de Gelder, Beatrice (Frontiers in Integrative Neuroscience, 2024)
Introduction We investigated the factors underlying naturalistic action recognition and understanding, as well as the errors occurring during recognition failures. Methods Participants saw full-light stimuli of ten different whole-body actions presented in three different conditions: as normal videos, as videos with the temporal order of the frames scrambled, and as single static representative frames. After each stimulus presentation participants completed one of two tasks—a forced choice task where they were given the ten potential action labels as options, or a free description task, where they could describe the action performed in each stimulus in their own words. Results While generally, a combination of form, motion, and temporal information led to the highest action understanding, for some actions form information was sufficient and adding motion and temporal information did not increase recognition accuracy. We also analyzed errors in action recognition and found primarily two different types. Discussion One type of error was on the semantic level, while the other consisted of reverting to the kinematic level of body part processing without any attribution of semantics. We elaborate on these results in the context of naturalistic action perception.